The relevance of social policies for democracy: preventing autocratisation through synergies between SDG 10 and SDG 16 - Julia Leininger; Anna Lührmann; Rachel Sigman (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Global threats to democracy – one of the world's most important forms of inclusive governance – have been rising recently. This paper assesses the effects of social and economic inequalities on autocratisation, meaning a decline in the democratic qualities of a political regime. The key question we study is whether different types, levels and changes in distributional inequalities (Sustainable Development Goal 10) contribute to the erosion of democratic institutions, thereby making governance less inclusive (SDG 16). The paper focusses, in particular, on distributional inequalities and more or less inclusive forms of governance (autocracy vs. democracy). Our findings suggest that conventional measures of income inequality – namely the Gini coefficient – have little to no discernible relationship to the likelihood of a decline in the democratic qualities of a political system. By contrast, inequalities in the provision of social services, particularly healthcare and education, have a clear and consistent relationship to the likelihood of autocratisation. As countries provide social opportunities more equally across their population, they are significantly less likely to experience a weakening of their democratic qualities. The findings of our empirical analyses are likely to receive the most interest from international actors who keep support for democracy high on their agendas, such as Sweden and Switzerland. However, the findings should matter to all those who are investing in the implementation of the 2030 Agenda, because achieving SDG 16 is decisive for the overall agenda.
Keywords: 330; Agenda 2030; Demokratie und Autokratie